A System Dynamics Approach to Optimizing Pension Insurance Pooling Governance: A Four-Dimensional Collaborative Path for Yingkou City - Zhang, Yuepeng (Scientific Journal of Technology, 2026)
Based on the author’s doctoral dissertation, this paper examines how system dynamics can be used to optimize regional pooling governance in China’s pension insurance system under unified provincial pooling rules. Using Yingkou City in Liaoning Province as the focal case and drawing on comparative evidence from the province’s 13 prefecture-level cities during 2015-2024, the paper integrates three layers of evidence: efficiency decomposition, influencing-factor identification, and dynamic pathway simulation. The preceding dissertation results show that Yingkou’s main efficiency bottleneck lies in pure technical efficiency (PTE) rather than scale efficiency (SE): the mean PTE is 0.60, clearly lower than the mean SE of 0.89, and during the 2020 shock year PTE declined to 0.54 while SE remained relatively stable at 0.88. This structure indicates that fragmented procedures, inconsistent information standards, weak interdepartmental coordination, and incomplete closed-loop supervision are more important obstacles than simple scale shortage. On this basis, a system dynamics framework is constructed with stock variables such as cumulative fund balance, insured population, benefit recipients, and governance-capacity stock; flow variables such as contribution revenue, fiscal subsidies, benefit expenditure, and risk handling; and four policy dimensions of policy adaptation, resource integration, technological empowerment, and regulatory assurance. The analysis shows that isolated digitalization is insufficient for sustained governance improvement. More stable gains require coordinated reform that first clarifies rules and closes high-frequency processes, then improves resource coordination and data connectivity, and finally embeds risk control and performance constraints into routine operations. The paper therefore proposes a phased optimization path for Yingkou that centers on benefit-eligibility certification, automatic cross-department verification, process reengineering, and continuous monitoring of process-performance indicators. The study contributes a practical city-level pathway for pension insurance governance and extends the dynamic-balance view of efficiency from measurement to simulation-based policy design.